Molecular cloning and expression of equine CYP1A2 in Escherichia coli - Mkabayi, Lithalethu (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2017)
Information regarding drug metabolism in veterinary species, especially horses, remains fragmented and incomplete. This information is essential for detection of metabolites of potential performance-enhancing substances in horseracing and for veterinary drug development. Equine liver microsomes have been used to study metabolism of a limited number of drugs, but these provide little information about individual drug metabolizing enzymes. Recombinant CYP enzyme systems are commonly used to determine contribution of individual CYP to metabolism of specific drugs. A limited number of recombinant equine CYPs have been expressed in insect cells and mammalian cell lines. However, there are no reports of recombinant equine CYP1A2 enzyme. In this study, equine CYP1A2 was identified, codon-optimized, cloned and expressed in E. coli BL21 cells. Multiple sequence alignments of equine CYP1A2 revealed an amino acid sequence identity of 83.69% to its human homolog which has previously been expressed in E. coli. The enzyme was expressed using both auto-induction and IPTG induction. Expressed equine CYP1A2 had a size of about 55 kDa, and was insoluble after cell lysis. Sarkosyl- solubilized CYP1A2 was purified using nickel affinity chromatography and gel filtration. For activity reconstitution, yeast NADPH-cytochrome P450 reductase was first expressed in E. coli BL21 cells and exhibited activity of 0.13 U/ml. Activity assay with Glo-P450 CYP1A2 assay kit indicated that CYP1A2 was inactive. Despite numerous attempts to obtain the activity, the CYP1A2 remained inactive. Although expression of equine CYP1A2 in E. coli produced non- catalytically active enzyme, this study could be used as the first step in an effort to fully develop a recombinant equine CYP1A2 system.
Keywords: Escherichia coli; Escherichia coli infections in animals; Cytochrome P-450; Cytochromes; Horses -- Effect of drugs on